Effect of dislocation distribution on the yield stress in ferritic steel under identical dislocation density conditions. (1st March 2020) - Tanaka, Yuki; Masumura, Takuro; Tsuchiyama, Toshihiro; Takaki, Setsuo
Abstract: Yield stresses of ferritic iron pre-deformed at 298 K and 213 K were compared under an identical dislocation density. The specimens pre-deformed at 213 K introduced uniformly distributed dislocations, while those at 298 K formed dislocation cell structure. After the pre-deformation, tensile tests and stress-relaxation tests were performed at room temperature. The specimens with uniformly distributed dislocations exhibited significantly lower yield stress and larger stress-relaxation than those with cell-structured dislocations even under almost same dislocation density. This result suggests that the uniformly distributed dislocations contain a large amount of mobile dislocations which can easily move at a low stress compared with the cell-structured dislocations. Graphical abstract: Image, graphical abstract